Writer’s Intention and Reader’s Interpretation from an Integrative-Methodological Standpoint - Gasparyan, Seda; Sargsyan, Nelli (Bulletin of Yerevan University B: Philology, 2025)
The present article targets the methodologies of literary text analysis with an emphasis on the exploration of writer’s intention and the way it is interpreted by readers. The main approaches covered in the present study are cognitive-stylistic analysis of texts with the objective of evaluating the aesthetics and disclosing the authorial intention of the text, hermeneutic interpretation with the purpose of studying the reader’s understanding of the text under discussion. The study of metaphors coined in J. London’s novel “White Fang” and the comparative analysis of their Armenian equivalents distinguished in the respective translation revealed that the integration of cognitive-stylistic, semantic and hermeneutic methods into the examination of literary texts contributes to the revelation of the author’s intention and determination of its interpretation. It can also be a possible solution for defining the criteria to assess and determine the aesthetic value of texts in the domain of verbal art.